2017
DOI: 10.1007/s11442-017-1404-6
|View full text |Cite
|
Sign up to set email alerts
|

Holocene environmental changes around Xiaohe Cemetery and its effects on human occupation, Xinjiang, China

Abstract: The Xiaohe Cemetery archaeological site (Cal. 4-3.5 ka BP) is one of the most important Bronze Age sites in Xinjiang, China. Although the surrounding environment is an extremely arid desert now, abundant archaeological remains indicate that human occupation was common during certain periods in the Holocene. Field investigations and laboratory analyses of a sediment profile near the Xiaohe Cemetery indicate that while the regional environment was arid desert throughout the Holocene there were three episodes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The southern part of Xinjiang consists of the Tarim Basin, a dry inland sea that now forms the Taklamakan Desert. Although mostly uninhabitable, the Tarim Basin also contains small oases and riverine corridors, fed by runoff from thawing glacier ice and snow from the surrounding high mountains 4 , 10 , 11 .
Fig.
…”
Section: Mainmentioning
confidence: 99%
“…The southern part of Xinjiang consists of the Tarim Basin, a dry inland sea that now forms the Taklamakan Desert. Although mostly uninhabitable, the Tarim Basin also contains small oases and riverine corridors, fed by runoff from thawing glacier ice and snow from the surrounding high mountains 4 , 10 , 11 .
Fig.
…”
Section: Mainmentioning
confidence: 99%
“…There is evidence for a widespread prehistoric culture in Xinjiang area, associated with a relatively wetter climate during the late Holocene (An et al, 2019). However, abrupt climate and environment changes might have led to the collapse of some civilizations, such as Xiaohe Culture (Zhang et al, 2017) and Loulan civilization (Fontana et al, 2019;Hao et al, 2019). A diatom record from Bosten Lake indicated that changes in hydro-climate was the main reason for the collapse of the Loulan Kingdom (Fontana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Especially when compared to the Palaeolithic period conditions under the influence of Younger Dryas impact hypothesis 28 , 88 , the Neolithic moisture and temperature conditions were superior and were conducive to human space expansion and settlement. The cold and dry climate (4.3–3.8 ka BP, 4.3 ka event) and its lagged influence on the early late Holocene in Xinjiang restricted the development of the Bronze Age in Xinjiang to some extent 89 – 91 . This climatic influence is also an important reason why the maximum elevation of settlements in the Bronze Age was 814 m lower than that during the Neolithic and why the settlement preference for rivers was different from that in the Neolithic, as evidenced by the decline of the Xiaohe Culture in Xinjiang 91 .…”
Section: Discussionmentioning
confidence: 99%